2021
DOI: 10.35241/emeraldopenres.13735.2
|View full text |Cite
|
Sign up to set email alerts
|

Financial literacy as a mediator of personal financial health during COVID-19: A structural equation modelling approach

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has become a global humanitarian challenge. This scourge has impacted people from all walks of life as well as every economic sector and activity, from travel to automotives, hotels to banking, and supply chain to retail. The pandemic has affected not only physical and mental health but also financial health. Studies have examined the pandemic’s economic impact, but very few have examined its impact on personal finances. Efforts to contain the pandemic’s spread,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Moreover, the analysis of the various dimensions of financial resilience using the KLS technique is presented in Table 8 . Specifically, our findings indicate that the dimensions of access to economic resources, financial resources, and financial literacy are associated with enhanced mental wellbeing, consistent with prior research ( Anand et al, 2021 ; Boyas et al, 2009 ; Clayton et al, 2015 ; Schreiter et al, 2020 ; Taft et al, 2013 ). One plausible explanation for this pattern of findings is rooted in the notion that individuals who possess a broad array of economic resources, such as savings, adept debt management skills, ample income, access to financial products and services, and financial literacy, are better equipped to effectively manage financial stressors and preserve their mental well-being as argued by Jayasinghe et al (2020) , Nanda and Banerjee (2021) and Stevenson et al (2022) .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, the analysis of the various dimensions of financial resilience using the KLS technique is presented in Table 8 . Specifically, our findings indicate that the dimensions of access to economic resources, financial resources, and financial literacy are associated with enhanced mental wellbeing, consistent with prior research ( Anand et al, 2021 ; Boyas et al, 2009 ; Clayton et al, 2015 ; Schreiter et al, 2020 ; Taft et al, 2013 ). One plausible explanation for this pattern of findings is rooted in the notion that individuals who possess a broad array of economic resources, such as savings, adept debt management skills, ample income, access to financial products and services, and financial literacy, are better equipped to effectively manage financial stressors and preserve their mental well-being as argued by Jayasinghe et al (2020) , Nanda and Banerjee (2021) and Stevenson et al (2022) .…”
Section: Discussionsupporting
confidence: 89%
“…Access to insurance products covering households against unexpected shocks has also been shown to reduce mental stresses and improve general wellbeing through increased financial stability in the US and Ghana ( Finkelstein et al, 2012 ; Gyasi et al, 2020 ). Anand et al (2021) claim that financial literacy improved the mental and financial wellbeing of Indian households during the COVID-19 pandemic. Furthermore, Zheng et al (2021) show that financial literacy has improved the mental health and general wellbeing of urban residents in China.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to (Anand et al, 2021), (Word Bank, 2020 financial knowledge contributes to the financial wellness of rural households and makes them more robust for tough times. The study also found that rural households have sound financial knowledge about different financial schemes and welfare programs.…”
Section: Discussionmentioning
confidence: 99%
“…The world has witnessed the adverse impact of the COVID-19 pandemic on all facets of life. The pandemic has heightened concerns for major socio-economic and political uncertainties as it directly or indirectly interrupts and hinders all events, activities, and processes about global development (Anand, Mishra, Verma & Taruna, 2021). The impact was even aggravated for developing countries, although developed countries also had their share of this same phenomenon.…”
Section: Introductionmentioning
confidence: 99%